What it takes to talk exploring developmental cognitive linguistics - Ibbotson, Paul (Cognitive linguistics research ;, 2020)
This book puts cognition back at the heart of the language learning process and challenges the idea that language acquisition can be meaningfully understood as a purely linguistic phenomenon. For each domain-general capacity placed under the spotlight - memory, attention, inhibition, categorisation, analogy and social-cognition - we establish the extent to which they shape the acquisition of sounds, words and grammar. As a cultural tool, linguistic knowledge has to pass through the bottleneck of what cognition can do, and allow, at any stage in development, and these self-imposed constraints can be adaptive for learning because they massively dampen the degrees of freedom available for linguistic generalizations. Without a developmental perspective it is difficult to make sense of what kind of thing language is, because learning constrains and shapes what kind of thing language can be. Language is special not because of some encapsulated module with content impenetrable and hived-off from the rest of cognition. It is special because of the forms it can take rather than the parts it is made of and because it could be nature?s finest example of cognitive recycling and reuse.